(untitled) (International journal of artificial intelligence, 2026)
This article discusses the theoretical and practical aspects of modeling soil settlement using the GeoFEM-UZ software. In civil and geotechnical engineering, determining foundation soil deformation is essential to ensure structural stability and safety. The study analyzes vertical and differential settlements using the finite element method. The functional capabilities, computational algorithms, and practical applications of the GeoFEM-UZ software are examined. The results demonstrate that numerical modeling provides higher accuracy compared to traditional analytical calculation methods.